PENGARUH KONFLIK PEKERJAAN-KELUARGA DAN KONFLIKKELUARGA-PEKERJAAN TERHADAP NIATAN KELUARMELALUI BURNOUT SEBAGAI VARIABEL MEDIASI (Studi Pada PT. Batang Apparel Indonesia) - Rahmawati, Putri Dwi; Yuniawan, Ahyar (Diponegoro Journal of Management, 2023)
ABSTRACT Intention to leave is one of the most researched issues in organizational analysisbecause a less competent employee can negatively impact an organization's competitiveadvantage. Incompetent employees can be caused by work-family conflicts andworkfamily conflicts when they work. In this study, burnout was used as an intermediaryvariable to define and assess the impact of work-family conflict and family-work conflict on the desire to cease working. This research was conducted at PT. Batang Apparel Indonesia. The populationof this research was employees who were married at PT. Batang Apparel Indonesia. Aproportionate random sampling approach was used to choose the samples, which included82 respondents. Data collection was carried out by distributing questionnaires usingaLikert scale. The data analysis technique utilized multiple regression. The results showed that (1) the decision to leave PT. Batang Apparel Indonesiawaspositively and significantly impacted by work-family conflict, (2) the intention to leavePT. Batang Apparel Indonesia was positively and significantly impacted by family-workconflict., (3) work-family conflict among PT. Batang Apparel Indonesia employees hadafavorable and substantial impact on the desire to leave, which was mediated by burnout, and (4) work-family conflict within PT. Batang Apparel Indonesia employees hadapositive and significant ef ect on the desire to leave, which was mediated by burnout